Ethnobotanical Study of Cosmetics of Baduy Community as a Recommendation for Biology Learning Content - Hendriyani, Mila Ermila; Yudiyanto, Yudiyanto; Fitriana, Desi Eka Nur; Survani, Rifki (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The use of plants by local communities as ingredients for daily needs such as medicine, art, cosmetics and others is known as ethnobotany. In the context of cosmetics, ethnobotany is concerned with the use of plants in the formulation of natural beauty and skin care products. This research aimed to examine the use of plants as cosmetic ingredients by the Baduy people, an ethnic group in the Banten Province of Indonesia, which is famous for its local wisdom and strong traditions. Data was obtained through observation, interviews and literature study. Key informants were selected using purposive sampling and selected traditional leaders (pu’un), the inner Baduy community, the outer Baduy community, and elders in the Baduy tribe. Data were analyzed using descriptive analysis. The research succeeded in identifying 22 species of plants used for body care activities such as body scrubs, facial masks, eye moisturizers, teeth cleaners, powder, lip color, perfume, soap, shampoo and hair oil. Knowledge and habits regarding the use of this plant have been passed down from generation to generation to maintain healthy skin, teeth, eyes and hair. The implementation of this research is used as a recommendation as content in Biology learning, especially in the project to strengthen the Pancasila students Profile through the preparation of teaching modules with a culturally responsive teaching (CRT) approach as an effort to preserve traditional knowledge, promote sustainability in the use of natural resources, and develop potential environmentally friendly cosmetic products.